Evaluation of the Total Quality of Tunnel Contour Using Projection Pursuit Dynamic Cluster Method. (11th March 2021) - Zou, Baoping; Xu, Zhipeng; Wang, Jianxiu; Luo, Zhanyou; Hu, Lisheng
Abstract : Full understanding of the total quality of tunnel contour after smooth blasting is quite a valuable task for accurately assessing the cost and construction rate. The traditional evaluation of tunnel contour quality which is always based on a single index such as the over/underbreak might not be rational enough because the contour quality at specific positions cannot completely stand for that of the total contour. Unreasonable evaluation of contour quality might cause construction delay or overbudget, as well as safety- and stability-related issues or even catastrophic accidents under some specific conditions. In this case, evaluating the total quality of tunnel contour considering all influential factors is of significance to smooth tunnelling. The aim of this paper is to develop a multiple indices system which can represent the total quality of the contour from different aspects, and then, the projection pursuit dynamic cluster (PPDC) method is utilized to quantitatively evaluate the total quality of tunnel contour. The multiple indices are screened using the principal component analysis (PCA) and gray correlation analysis (GCA). The selected 9 indices to form the multiple indices system include the maximum overbreak, average overbreak, maximum underbreak, maximum size of step between two guns, area of overbreak, measured area, rate of overbreak, volume of overbreak, and blast hole utilization factor. The total quality of tunnel contour is quantitatively defined with 5 levels by using the dynamic cluster (DC) analysis. With the obtained values of the 9 indices, the total quality of the tunnel contour could be determined quantitatively according to the calculated projection eigenvalues. The result of the total quality of tunnel contour obtained using the proposed method is much more accordant with the site than that based on a single evaluation index. The proposed method will offer a promising alternative to fully understand the total quality of tunnel contour.